Epithelioid Angiomyolipoma of Liver with an Inflammatory Component: A Case Report - Jyothi C. R.; Dhanya P. Menon; Joy Augustine; A. K. Abdul Siyad (Case Reports in Hepatology)
Angiomyolipomas (AMLs) are benign mesenchymal tumors seen in kidneys in association with tuberous sclerosis. They are uncommon in liver. Angiomyolipomas of liver show great histological diversity and various types and patterns are described. Among them, epithelioid and inflammatory angiomyolipomas are rare. We report a case of epithelioid angiomyolipoma of Liver with an inflammatory component.